Experimental study on controlled hot surface assisted compression ignition (HSACI) in a naturally aspirated single cylinder gas engine. (March 2023) - Judith, Joern Alexander; Kettner, Maurice; Koch, Thomas; Schwarz, Danny; Klaissle, Markus
Homogeneous charge compression ignition (HCCI) promises lowNO x emissions and high efficiency due to fast combustion at low temperatures. However, the control of combustion timing represents a serious challenge due to the lack of dedicated ignition control parameters. This challenge is addressed in this work by means of a hot surface ignition (HSI) system, whose core element consists of a shielded, electrically heated ceramic glow plug. In this approach, termed as hot surface assisted compression ignition (HSACI), a small portion of mixture is thought to ignite in the vicinity of the shielded glow plug and to subsequently propagate to the main combustion chamber in order to initiate bulk-gas auto-ignition. Adjusting the hot surface temperature enables to either advance or retard the onset of combustion and thus, allows to control combustion timing. This paper presents experimental results of initial engine trials, using the HSACI concept in a naturally aspirated single cylinder natural gas engine. Measurements were conducted at a constant engine speed of 1400 l/min and include intake air temperatures in the range of 150–175°C and relative air-fuel ratios (λ ) from 2.0 to 2.8. Results show that the HSI system enables combustion under conditions, which do not allow for pure HCCI operation. Moreover, the combustion timing can be actively controlled within certain limits by changing the HSI temperature. Increasing cycle-to-cycle variations limit stable operation at lower temperatures, while a transition to pure HCCI is found at intake temperatures beyond 170°C. The applicableλ range is limited by knocking or uncontrolled combustion toward the rich side and instable operation toward the lean side. Loss analysis points out that wall heat flow and imperfect combustion represent the dominant loss mechanisms. Heat release analysis reveals two pronounced phases, indicating initial flame propagation and subsequent auto-ignition similar to spark assisted compression ignition (SACI).